2000
DOI: 10.1111/j.1747-6593.2000.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Groundwater Abstraction Cause Degradation of Rivers and Wetlands?

Abstract: There is a widely held belief that, over the last few decades, many rivers and wetlands have been significantly degraded. Clearly, groundwater abstraction has had a detrimental effect.However, other pressures such as channelisation, sedimentation, reduced rainfall, poor site management or land-use change can be contributing factors. Various policy responses are reviewed and some examples are given. It is concluded that, whilst groundwater abstraction does cause river and wetland degradation, the degree of degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…This may also need to consider any inflows between the two, especially major tributaries, which may involve rainfall-runoff forecasting (Acreman, 1996). Particular challenges exist for groundwater abstractions due to the time lag between groundwater abstraction and its impact on river flows (Acreman et al, 2000).…”
Section: Active Managementmentioning
confidence: 99%
“…This may also need to consider any inflows between the two, especially major tributaries, which may involve rainfall-runoff forecasting (Acreman, 1996). Particular challenges exist for groundwater abstractions due to the time lag between groundwater abstraction and its impact on river flows (Acreman et al, 2000).…”
Section: Active Managementmentioning
confidence: 99%
“…More recently, increasing consideration has been given to additional causes of low flows besides abstraction. Acreman et al 3 put…”
Section: Introductionmentioning
confidence: 99%
“…For example, 27 of the 40 rivers identified had low flows attributed to public water supply abstraction or to summer spray irrigation under 'licences of right'. 3 Owen 4 proposed that over-abstraction of groundwater was an important cause of unsatisfactorily low flows in groundwaterdominated rivers. In particular, his comparison of the River Ver and the River Chess, both chalk-stream tributaries of the River Colne in Hertfordshire, UK, concluded that abstractions were having a major influence on the Ver's flows.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a shows the location of major dams in the eastern US (defined as those 50 feet or more in height, or with a normal storage capacity of 5000 acre feet ( ∼ 6 200 000 m 3 ) or more, or with a maximum storage capacity of 25 000 acre feet (∼ 30 800 000 m 3 ) or more; USACE, 2012). Generally dams and reservoirs are considered the largest man-made regulations on streamflow, but other sources include farm ponds, surface water extraction, inter-basin transfers, and wastewater treatment plant discharge (e.g., Walker and Thoms, 1993;Acreman et al, 2000;Brandes et al, 2005;Thomas, 2006;Deitch et al, 2009;Kustu et al, 2010).…”
mentioning
confidence: 99%